ANALISIS PEMBIAYAAN MACET PADA BPRS MITRA AGRO USAHA - Rahma Aulia Nazwa; Noorikha Pandayahesti Saputri; Eki Tiyas Nurulia (Program Studi Ekonomi Syariah, 2026)
Non-performing financing (NPF) is one of the main challenges faced by Islamic Rural Banks (BPRS), including BPRS Mitra Agro Usaha Lampung. This issue arises from various external and internal factors. External factors include economic conditions, government policies, and natural disasters, while internal factors involve suboptimal credit analysis and weak monitoring of customers. High levels of non-performing financing can disrupt the bank's financial stability and reduce customer trust in Islamic financial institutions. Therefore, effective handling strategies that align with Sharia principles are crucial. The purpose of this study is to analyze the factors causing non-performing financing, evaluate the handling mechanisms implemented by BPRS Mitra Agro Usaha Lampung, and assess their compliance with Sharia principles. This research uses a descriptive qualitative method with data collected through interviews, observations, and documentation. The results show that the handling strategies include issuing warning letters, conducting discussions (musyawarah) with customers, restructuring financing, sealing collateral, and auctioning collateral as a last resort. These strategies align with Sharia principles, emphasizing justice, transparency, and the prohibition of riba. However, the NPF rate at BPRS Mitra Agro Usaha Lampung remains relatively high, at 11%, indicating the need for improved risk analysis, regular monitoring, and the development of an early warning system to detect potential risks sooner